2020
DOI: 10.1096/fj.201902643r
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxytyrosol stimulates neurogenesis in aged dentate gyrus by enhancing stem and progenitor cell proliferation and neuron survival

Abstract: The dentate gyrus of the hippocampus is one of two brain areas generating throughout life new neurons, which contribute to the formation of episodic/associative memories. During aging, the production of new neurons decreases and a cognitive decline occurs. Dietary factors influence neuronal function and synaptic plasticity; among them the phenolic compound hydroxytyrosol (HTyr), present in olive oil, displays neuroprotective effects. As age impacts primarily on the hippocampus‐dependent cognitive processes, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 82 publications
(185 reference statements)
2
20
0
Order By: Relevance
“…A recent in vivo study evidenced that HT stimulates neurogenesis in aged dentate gyrus by enhancing stem and progenitor cell proliferation and neuron survival (69).…”
Section: Referencesmentioning
confidence: 99%
“…A recent in vivo study evidenced that HT stimulates neurogenesis in aged dentate gyrus by enhancing stem and progenitor cell proliferation and neuron survival (69).…”
Section: Referencesmentioning
confidence: 99%
“…Olive oil phenols have powerful antioxidant, anticancer, and anti-inflammatory activity [ 3 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. The presence and content of these compounds are the basis of a health claim approved by the European Food Safety Authority (EFSA) in 2012 [ 19 ], which states that “olive oil polyphenols contribute to the protection of blood lipids from oxidative stress”.…”
Section: Introductionmentioning
confidence: 99%
“…It appears that stem cells can be reactivated in the dentate gyrus or SVZ by appropriate stimuli, under conditions, in apparent paradox, favoring their depletion, such as aging or depression, i.e., when neurogenesis is lower, and/or after deletion of quiescence-maintaining genes. For instance, HTyr or running activate stem cells in aged dentate gyrus or aged SVZ, respectively (Blackmore et al, 2009;D'Andrea et al, 2020). Actually, the preservation of the quiescent state of stem cells appears less effective when the system is aging or carrying mutations, i.e., when a neurogenic stimulus can activate also stem cells.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, in a recent study of the effect on dentate gyrus cells of hydroxytyrosol (HTyr), a natural anti-oxidant phenolic compound present in extra virgin olive oil, we observed that HTyr in adult mice increases the number of new neurons by enhancing their survival without effect on the proliferation of stem and progenitor cells (D'Andrea et al, 2020; Table 1). However, in aged mice as well as in the Btg1 knockout neural aging model, HTyr increases not only the survival of new neurons and improves their integration into memory circuits, but also strongly increases the proliferation of stem and progenitor cells and reduces aging markers such as lipofuscin and Iba-1 (D'Andrea et al, 2020 ; Tables 1, 3). Thus, HTyr is able to counteract the effect of aging on neurogenesis.…”
Section: Nutrients As Activators Of Stem Cells In Adult and Aged Dentmentioning
confidence: 99%